2016
DOI: 10.1038/mtm.2016.78
|View full text |Cite
|
Sign up to set email alerts
|

Significant changes in endogenous retinal gene expression assessed 1 year after a single intraocular injection of AAV-CNTF or AAV-BDNF

Abstract: Use of viral vectors to deliver therapeutic genes to the central nervous system holds promise for the treatment of neurodegenerative diseases and neurotrauma. Adeno-associated viral (AAV) vectors encoding brain-derived neurotrophic factor (BDNF) or ciliary derived neurotrophic factor (CNTF) promote the viability and regeneration of injured adult rat retinal ganglion cells. However, these growth-inducing transgenes are driven by a constitutively active promoter, thus we examined whether long-term AAV-mediated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…Effects of gene knockdown on downstream cell signaling pathways could have unpredictable changes on the functional outcome measures we employ to assess effects of gene silencing. While we did not detect any effects of the AAV siRNA vectors on hippocampal-dependent behavioral tests, other studies have found a single injection of AAV alters endogenous gene expression a year post-injection [ 76 ]. Thus, our study does not preclude long term genomic changes that may result from acute AAV siRNA-mediated reduction in degenerating neurons in the hippocampus; these changes may preserve other cognitive functions not tested in our study.…”
Section: Discussioncontrasting
confidence: 88%
“…Effects of gene knockdown on downstream cell signaling pathways could have unpredictable changes on the functional outcome measures we employ to assess effects of gene silencing. While we did not detect any effects of the AAV siRNA vectors on hippocampal-dependent behavioral tests, other studies have found a single injection of AAV alters endogenous gene expression a year post-injection [ 76 ]. Thus, our study does not preclude long term genomic changes that may result from acute AAV siRNA-mediated reduction in degenerating neurons in the hippocampus; these changes may preserve other cognitive functions not tested in our study.…”
Section: Discussioncontrasting
confidence: 88%
“…However the resultant long-term upregulation of protein kinases such as mTOR, a key regulator of protein translation in neurons, leads to some aberrant growth [ 48 ] and progressive changes in the growth of cells, their dendrites, and their axons [ 46 ]. This is not dissimilar to the effect of long-term (up to one year) AAV-mediated expression of CNTF on retinal ganglion cells, where there are not only changes in the dendritic morphology of transduced and neighboring nontransduced cells [ 51 ], but there is also altered expression of endogenous retinal genes [ 52 ]. Whether such effects are also seen in cortical neurons transduced with AAV-CNTF is yet to be determined, but this is an important topic for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…AKT silencing was previously reported to be associated with hypomyelination ( 38 ). The expression of PLCG2 was revealed to be sensitive to ciliary neurotrophic factor ( 39 ), a cytokine which may promote peripheral nerve regeneration ( 40 ). Consequently, the NK cell mediated cytotoxicity and BCR signaling pathways may be associated with PNS myelination through FCGR, RAC2 and PLCG2.…”
Section: Discussionmentioning
confidence: 99%